Short Communication: The biodiversity of aquatic organisms in Anak Laut Lake, Aceh Singkil District, Indonesia - AHMAD MUHTADI; RUSDI LEIDONALD; OKTI YOLANDA; RUHHIYAH HARAHAP; NENENG PRATIWI MATONDANG; KHAISYA PUTRI; LAURA F. M. SIMAMORA; GABRIYELLA SITOMPUL (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Muhtadi A, Leidonald R, Yolanda O, Harahap R, Matondang NP, Putri K, Simamora LFM, Sitompul G. 2023. Short Communication: The biodiversity of aquatic organisms in Anak Laut Lake, Aceh Singkil District, Indonesia. Biodiversitas 24: 4837-4844. Anak Laut Lake is a unique and strategic coastal lake, significantly recognized for its diverse marine biota and the potential to be a spawning, nursery, and feeding ground. Therefore, this research aimed to determine the types of aquatic organisms, including plankton, fish, crustaceans, benthos, seagrasses, and mangroves in Anak Laut Lake. The experiment was conducted in October 2022 in the Anak Laut Lake ecosystem, North Singkil Sub-district, Aceh Singkil District, Aceh Province, Indonesia. The plankton was taken using a plankton net tool, extracted vertically from a depth of 2 m, and pulled to the surface. Fish and crustaceans were observed and caught with purse seines, ring nets, and gill nets. Benthic organisms were directly observed on the edge of the lake, along with the identification of mangroves, while at the bottom, the fishermen dove into the water. The data obtained were analyzed descriptively and compared with similar research. The results showed a rich biodiversity in Anak Laut Lake, with at least 165 species/genera of aquatic biota, 9 species of mangroves, and 2 Seagrass species. The marine nekton found consisted of fish (55 species), shrimp (3 species), and crabs (10 species). The macrozoobenthos found in Anak Laut Lake consisted of 13 species of clams, 12 gastropods, 3 sea cucumbers, 2 sand dollars, 2 horseshoe crabs, and 1 sea urchin. Various species of aquatic biota whose existence was threatened in nature and found in this lake included golden sea cucumber (Stichopus herrmanni), seahorse (Hippocampus comes and Hippocampus kuda) with Vulnerable status (VU), tap ray (Maculabatis gerrardi), and sand cucumber (Holothuria scabra) with Endangered species status (EN). This shows that this coastal lake is an important and crucial habitat for several species that are vulnerable to extinction. For this reason, in the future, further studies are needed regarding the habitat characteristics and spatial and temporal distribution of aquatic organisms in Lake Laut, so that more appropriate management can be implemented for the sustainability of the lake.